Debt to Equity Ratio (DER) dan Return On Asset (ROA) untuk Meningkatkan Harga Saham - Kurniasih, Sarah; Surachim, Ahim (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
The purpose of this study is to inform impact Debt to Equity Ratio (DER) and Return On Equity (ROA) to Stock Price. The research does in range of time less of one year, in order to research design that used is time interest earned. This research that used to sampling technique time series The research is used descriptive approach and verificative with explanatory research and data analysis technique that used multiple linear regression. The results of this study is Debt to Equity Ratio (DER) and Return On Asset (ROA) has impact is significant to Stock Price. The differences is decided in independent variable object, and reaserch method. Population and research sample, research period, measure instrument and research result, and source of theory and international journal and international book.Â